login

Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 61st year, we have over 378,000 sequences, and we’ve reached 11,000 citations (which often say “discovered thanks to the OEIS”).

A246694
Triangle read by rows: T(n,k) = T(n,k-2) + 1 if n > 1 and 2 <= k <= n; T(0,0) = 1, T(1,0) = 1, T(1,1) = 2; if n > 1 is odd, then T(n,0) = T(n-1,n-2) + 1 and T(n,1) = T(n-1,n-1) + 1; if n > 1 is even, then T(n,0) = T(n-1,n-1) + 1 and T(n,1) = T(n-1,n-2) + 1.
7
1, 1, 2, 3, 2, 4, 3, 5, 4, 6, 7, 5, 8, 6, 9, 7, 10, 8, 11, 9, 12, 13, 10, 14, 11, 15, 12, 16, 13, 17, 14, 18, 15, 19, 16, 20, 21, 17, 22, 18, 23, 19, 24, 20, 25, 21, 26, 22, 27, 23, 28, 24, 29, 25, 30, 31, 26, 32, 27, 33, 28, 34, 29, 35, 30, 36, 31, 37, 32
OFFSET
0,3
COMMENTS
As an array, for each m, row 2*m has m odd numbers and m+1 even numbers; row 2*m-1 has m odds and m evens. As a sequence, every positive integer n occurs exactly twice, separated by floor((n+1)/2) other numbers.
LINKS
FORMULA
T(n, k) = 1 + floor(n/2) * (1+(-1)^k) / 2 + (floor(n/2))^2 + (2*k - 1 + (-1)^k) / 4 + (1-(-1)^n) * (1-(-1)^k) * n / 4. - Werner Schulte, Nov 16 2024
From Stefano Spezia, Nov 17 2024: (Start)
T(n, k) = (6 + (-1)^k + (-1)^(k+n) + 4*k + 2*n*(1 + (-1)^(k+n) + n))/8.
G.f.: (1 - x^3*y + x^7*y^3 + x^4*(1 - 2*y^2) - x^5*y*(1 - y^2))/((1 - x)^3*(1 + x)^2*(1 - x*y)^3*(1 + x*y)). (End)
EXAMPLE
First 8 rows:
1
1 ... 2
3 ... 2 ... 4
3 ... 5 ... 4 ... 6
7 ... 5 ... 8 ... 6 ... 9
7 .. 10 ... 8 .. 11 ... 9 .. 12
13 .. 10 .. 14 .. 11 .. 15 .. 12 .. 16
13 .. 17 .. 14 .. 18 .. 15 .. 19 .. 16 .. 20
MATHEMATICA
z = 25; t[0, 0] = 1; t[1, 0] = 1; t[1, 1] = 2;
t[n_, 0] := If[OddQ[n], t[n - 1, n - 2] + 1, t[n - 1, n - 1] + 1];
t[n_, 1] := If[OddQ[n], t[n - 1, n - 1] + 1, t[n - 1, n - 2] + 1];
t[n_, k_] := t[n, k - 2] + 1; Flatten[Table[t[n, k], {n, 0, z}, {k, 0, n}]](*A246694*)
PROG
(Haskell)
a246694 n k = a246694_tabl !! n !! k
a246694_row n = a246694_tabl !! n
a246694_tabl = [1] : [1, 2] : f 1 2 [1, 2] where
f i z xs = ys : f j (z + 1) ys where
ys = take (z + 1) $ map (+ 1) (xs !! (z - i) : xs !! (z - j) : ys)
j = 3 - i
-- Reinhard Zumkeller, Sep 03 2014
CROSSREFS
Cf. A246695 (row sums), A174114 (central terms).
Cf. A002620 (main diagonal and first subdiagonal), A377802.
Sequence in context: A361000 A283368 A199474 * A054384 A026400 A026409
KEYWORD
nonn,easy,tabl
AUTHOR
Clark Kimberling, Sep 01 2014
EXTENSIONS
Edited by M. F. Hasler, Nov 17 2014
STATUS
approved